Four new species of Penottus Distant (Hemiptera: Tingidae) from China - Dang, Kai; Li, Chuanren; Bu, Wenjun (Zootaxa, 2012)
Six species of Penottus Distant, 1903 (Heteroptera: Tingidae) from China are treated in this paper, in which Penottustibetanus Drake and Maa, 1954 (described from Tibet) is newly recorded from Hubei Province, and four species aredescribed as new: Penottus bisinuatus sp. n., Penottus cassideus sp. n., Penottus fujianensis sp. n., and Penottus tuberculiformis sp. n. A key to the species occurring in China is provided.